2021
DOI: 10.1038/s41699-020-00186-w
|View full text |Cite
|
Sign up to set email alerts
|

Multiple machine learning approach to characterize two-dimensional nanoelectronic devices via featurization of charge fluctuation

Abstract: Two-dimensional (2D) layered materials such as graphene, molybdenum disulfide (MoS2), tungsten disulfide (WSe2), and black phosphorus (BP) provide unique opportunities to identify the origin of current fluctuation, mainly arising from their large surface areas compared with those of their bulk counterparts. Among numerous material characterization techniques, nondestructive low-frequency (LF) noise measurement has received significant attention as an ideal tool to identify a dominant scattering origin such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 56 publications
(88 reference statements)
0
3
0
Order By: Relevance
“…In this study we combine a classical electrochemical method with opportunities of machine learning (ML) technique which has already proved to be effective and promising. , Machine learning is a technology that allows a computer to independently acquire information from data. It enables a computer system to respond to an input based on the optimization (through a large amount of data and computing power) of a statistical model and to make predictions with reasonable accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…In this study we combine a classical electrochemical method with opportunities of machine learning (ML) technique which has already proved to be effective and promising. , Machine learning is a technology that allows a computer to independently acquire information from data. It enables a computer system to respond to an input based on the optimization (through a large amount of data and computing power) of a statistical model and to make predictions with reasonable accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, machine learning (ML) has shown the capability of extracting interpretable models from scientific data automatically [ 32 ]; it has been increasingly employed in the design and control of robots [ 33 ], actuators [ 34 ] and pumps [ 35 ]. Material equivalization of composite materials in 3D and 2D structures is a major aspect of ML research.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, an artificial-intelligence-based approach has been used for data analysis. This machine learning (ML) has been used in a wide range of applications such as voice search, image recognition, molecular/materials science, , and photonics devices. , It has demonstrated that ML can provide an efficient optimization and guidance for classification of scientific data. …”
Section: Introductionmentioning
confidence: 99%